(untitled) (Journal of International Relations and Peace, 2024)
Leadership is very important in educational administration because of its far-reaching effects on the accomplishments of the school programmes and goals attainment. It is generally believed that education leadership has a major connectivity with the school outputs, as well as teachers’ productivity. Thus, amidst the growing concerns for declining quality of education in Nigeria. This study investigated the impact of leadership styles of principals on the productivity of teachers in public secondary schools in Nigeria referencing some selected government-owned secondary schools in Ondo State. The study adopted quantitative methodology where collected data were analyzed by descriptive cross- sectional research design. The primary data were collected from the questionnaire given to 300 respondents comprising 270 classroom teachers and 30 school principals purposively selected from 9 secondary schools from the study area through a multi-stage sampling technique. The Secondary data were obtained from internet materials, schools records, government published articles, newspapers, textbooks and personal observations. The study relied on path - goal leadership theory as a theoretical fulcrum. The findings of the study revealed that poor leadership attributes commonly found among the school principals in secondary schools are responsible for the low teachers’ productivity in Ondo state public schools. The study further revealed that the low productivity of teachers affects the academic performance of secondary schools students in both internally and externally- administered examinations. The study concluded that the existing negative correlation between leadership styles of secondary school principals and classroom teachers in Ondo State portends a great danger for education advancement and academic performance of students. Hence, it was suggested that the governments and stakeholders must jointly embrace and reinvigorate the performances appraisal system in the Nigerian Civil Service and organize trainings that will enhance leadership development among the school principals in Ondo State.